2019
DOI: 10.4081/ijfs.2019.8263
|View full text |Cite
|
Sign up to set email alerts
|

Contamination level and exposure assessment to Aflatoxin M1 in Jordanian infant milk formulas

Abstract: Aflatoxin M1 (AFM1) is a principal hydroxylated-aflatoxin B1 (AFB1) metabolite, and has been classified as possible human carcinogen (group 2B). The aim of this study was to survey the contamination level, estimated daily intake (EDI) and tolerable daily intake % (TDI%) of AFM1 in Jordanian infant milk formulas. A total of 120 samples, 48 starter and 72 follow-on formula samples were collected and analyzed using ELISA technique. Of the 120 surveyed samples, 58 (48.33%) were AFM1-positive and exceeded the EU ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
8
2
Order By: Relevance
“…In this sense, Li et al [14] detected the presence of AFM 1 in powder base for infant formulae in China, evaluating a total of 1207 samples, with 56 samples being positive for the toxin without passing the Chinese limit (62.5 ng/kg). Awaisheh et al [23] determined the AFM 1 content in infant formulae (120 samples; 48 starter and 72 follow-on formulae) distributed in Jordan, with 58 positive samples for the toxin presence, with a media of 69 and 84 ng/kg for the starter and follow-on formulae, respectively.…”
Section: Occurrence Of Afm 1 In Infant Formulaementioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Li et al [14] detected the presence of AFM 1 in powder base for infant formulae in China, evaluating a total of 1207 samples, with 56 samples being positive for the toxin without passing the Chinese limit (62.5 ng/kg). Awaisheh et al [23] determined the AFM 1 content in infant formulae (120 samples; 48 starter and 72 follow-on formulae) distributed in Jordan, with 58 positive samples for the toxin presence, with a media of 69 and 84 ng/kg for the starter and follow-on formulae, respectively.…”
Section: Occurrence Of Afm 1 In Infant Formulaementioning
confidence: 99%
“…However, when major lactating groups gain weight and reduce the follow-on formula intake (i.e., two years old), the EDI is reduced up to 4.28 ng/kg bw/day. Awaisheh et al [23] have evaluated the infant formulae consumed in Jordan, presenting an EDI of 1.57 and 1.55 ng/kg bw/day for infants aged six and 12 months, respectively. On the other hand, Ismail et al [25] reported an EDI value of 4.1 ng/kg bw/day for children aged one to three years in Pakistan.…”
Section: Infant Formulae Daily Intake By Age Groupmentioning
confidence: 99%
“…8,9 Indeed, AFB1 metabolite known as aflatoxin M1 (AFM1) is frequently found in milk, samples of cord blood, and colostrum in pregnant women, which signify the possibility of prenatal contact to AFB1 in humans. 1012 Aflatoxins were reportedly detected in semen samples (40%) obtained from infertility clinics amid a higher chance of sperm anomaly compared with fecund men living within a locality in Nigeria. 13 Moreover, data from experimental animals have demonstrated that AFB1 may be an essential risk factor for male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…AFM1 is found worldwide; however, its levels vary considerably in different regions, depending on the milk production system, climate, and the dairy species [ 12 ]. These problems are much more serious in low-income countries, where their presence can be common and even extreme [ 13 ], including contamination of breast milk [ 14 ] and infant formulas [ 15 ]. For this reason, the permanent study of AFM1 [ 16 ] is necessary to protect human health and trade [ 17 ].…”
Section: Introductionmentioning
confidence: 99%